Comparative Evolutionary Genomics Unveils the Molecular Mechanism of Reassignment of the CTG Codon in Candida spp. - Massey, Steven E.; Moura, Gabriela; Beltrão, Pedro; Almeida, Ricardo; Garey, James R.; Tuite, Mick F.; Santos, Manuel A.S. (Genome Research, 2003)
Using the (near) complete genome sequences of the yeastsCandida albicans, Saccharomyces cerevisiae, andSchizosaccharomyces pombe, we address the evolution of a unique genetic code change, which involves decoding of the standard leucine-CTG codon as serine in Candida spp. By using two complementary comparative genomics approaches, we have been able to shed new light on both the origin of the novel Candida spp. Ser-tRNACAG, which has mediated CTG reassignment, and on the evolution of the CTG codon in the genomes of C. albicans,S. cerevisiae, and S. pombe. Sequence analyses of newly identified tRNAs from the C. albicans genome demonstrate that the Ser-tRNACAG is derived from a serine and not a leucine tRNA in the ancestor yeast species and that this codon reassignment occurred ∼170 million years ago, but the origin of the Ser-tRNACAG is more ancient, implying that the ancestral Leu-tRNA that decoded the CTG codon was lost after the appearance of the Ser-tRNACAG. Ambiguous CTG decoding by the Ser-tRNACAG combined with biased AT pressure forced the evolution of CTG into TTR codons and have been major forces driving evolution of the CTN codon family in C. albicans. Remarkably, most of the CTG codons present in extant C. albicans genes are encoded by serine and not leucine codons in homologous S. cerevisiae and S. pombe genes, indicating that a significant number of serine TCN and AGY codons evolved into CTG codons either directly by simultaneous double mutations or indirectly through an intermediary codon. In either case, CTG reassignment had a major impact on the evolution of the coding component of the Candidaspp. genome.[Supplemental material is available online at http://www.genome.organd at http://www.bio.ua.pt/genomica/Lab/Genomedata.html. The following individuals kindly provided reagents, samples, or unpublished information as indicated in the paper: N. Federspiel.]